People walking up to church entrance. (1949)
Opening session for the 40th NAACP Convention took place at the Second Baptist Church, 2412 Griffith Ave., in South Central Los Angeles. Norman F. Marsh designed the building along with black architect Paul R. Williams. The church has figured prominently in the African-American civil rights movement